PERANCANGAN SISTEM INFORMASI PENJUALAN DAN PEMESANAN PRODUK OUTSOLE BERBASIS WEB (STUDI KASUS PT. RUKUN DJAYA SOLINDO) - Laily Eka Fitriawati; Thoyyibah Tanjung (CV. Multi Kreasi Media, 2023)
Online sales and ordering is important for an agency or company. In selling PT. Rukun Djaya Solindo still uses the manual method. There are several obstacles that occur in using this procedure, including the existence of customers who manipulate orders at the time of purchase, resulting in some less factual financial reports and the ordering process using books also requires the Administration to re-enter sales data into excel, so that the recapitulation process becomes inefficient. Therefore we need a web-based sales and ordering that can collect and manage data so that sales can run quickly, effectively and efficiently. Created with the waterfall method, this sales and ordering application is designed in a simple and user friendly manner. The software used in making this sales and ordering application include PHP, MySQL and Xampp. With this application, it can make it easier for admins to make sales and orders.